Universal hearing screening for neonatal intensive care unit infants : a retrospective study comparing results of Automated Auditory Brainstem Response and presence of risk factors for hearing loss with audiological assessment results - Zakaria, Nur 'Azzah (2012)
Objective: Implementation of universal newborn hearing screening (UNHS) in the neonatal intensive care unit (NICU) at Royal Children Hospital (RCH) by the Victorian Infant Hearing Screening Program (VIHSP) provided an opportunity for Automated Auditory Brainstem Response (AABR) screening results to be compared with formal audiological assessment results. This study aimed to ascertain the performance of risk factors for hearing loss in relation to detecting permanent hearing loss as the risk factors available in other studies showed large variability.